Tinjauan Hukum terhadap Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) Industri dan Dampaknya terhadap Lingkungan: Legal Review of the Management of Industrial Hazardous and Toxic Waste (B3) and its Impact on the Environment - Irgi Dwi Fahrezi; Muhammad Ilham (Information Technology and Science (ITScience), 2026)
The issue of environmental pollution has become an important topic in global discussions regarding ecosystem sustainability. The main problem is the management of industrial waste, especially Hazardous and Toxic Materials (B3) waste, which has been stated in Law No. 32 of 2009 concerning Environmental Protection and Management (PPLH). Article 1, paragraph 22 states: Hazardous and toxic waste, hereinafter referred to as B3 Waste, is the residue of a business and/or activity that contains B3. If not managed properly, it can cause serious impacts on the environment. This type of research uses a normative juridical research type, using a descriptive analytical statutory approach, data sources using secondary data, and data collection tools using literature studies, then analyzed using qualitative methods. The results of the study found that legal regulations in the management of B3 waste in industry have experienced quite good development in Indonesia. However, the implementation of this regulation still faces various challenges, including inadequate infrastructure, high costs, and weak supervision and law enforcement. Improvements in the law enforcement system are expected to create a balance between industrial growth and environmental sustainability. The government's efforts in managing hazardous and toxic waste have had significant positive impacts, particularly in reducing pollution, increasing industry awareness, and protecting public health. However, challenges in infrastructure and technology implementation still need to be addressed for this policy to be more effective.